Օտարման առանձնահատկությունները «Ցանցային հասարակության» մեջ - Սարգիս Կարապետյան (ՀՀ ԳԱԱ հրատ.)
В статье представлена проблема политического отчуждения в информационном обществе. В этой связи анализируется процесс виртуализации не только экономики, но и политики. Показывается как политика превращается в «политику образов». В статье рассматривается механизм такого превращения. The article presents the problem of political alienation in the information society. In this regard, not only the economic but also political process of virtualization is being analyzed. It displays how politics becomes a “policy of images.” The article discusses the mechanisms of such transformation.
Keywords: Social Sciences; Sociology